THE INCIDENCE AND IMPACT OF CATTLE RUSTLING IN SOME RURAL COMMUNITIES OF KATSINA STATE, NIGERIA. - Abdulrashid, I.; Saifullahi, S. I.; Amir, A. (FUDMA Journal of Sciences, 2023)
This study examined the impact of cattle theft on socioeconomic wellbeing of rural farmers in Katsina state. A cross-sectional data of 1488 respondent selected from six purposively sampled LGAs (Batsari, Danmusa, Faskari, Kankara, Sabuwa and Safana) was obtained via a well-structured questionnaire and Focus Group Discussions. The survey data was analysed with inferential statistics using classical independent t-test in which the socioeconomic variables of the respondents before the cattle rustling were compared with the socioeconomic variables during the cattle rustling period. It was found that, despite the fact that cattle rustling has led to loss of life and displacement of people to other safe places, there is no significant reduction of the people living in such rural communities. This indicates that, there is no significant reduction of cattle ownership by the people before and after the cattle rustling. However, it has been found that a significant difference in income level of the respondent exists. Therefore, cattle rustling could further deepen the vicious cycle of poverty in rural areas of Katsina state. Some innovative ways of combating cattle theft in form of Community Cattle Ranch and Radio Frequency Identifier should be carefully adopted.
Keywords: Cattle rustling, economic wellbeing, famers, rural community